Analisis Keaktifan Belajar Peserta Didik Melalui Media Ular Tangga Mata Pelajaran IPAS Kelas IV - Nurul Dian Pertiwi; Farida Nursyahidah; Arfilia Wijayanti; Karunia Suhono (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The purpose of this study was to find out the active learning of students through the medium of snakes and ladders in science subjects. This type of research is a qualitative descriptive research. The source of the research data came from fourth grade students at SDN Sarirejo. The data used in this study are the results of observations, interviews, and documentation of fourth grade students related to students' active learning problems. The analytical method used is descriptive qualitative. Based on the findings of the research results, the following conclusions can be drawn. Based on the results of the research on the activeness of students using snakes and ladders media in science subjects, the average activity of students in class IV A was 72.7%, so it was included in the good criteria. Students tend to be interested in following the learning process. In this case, the teacher acts as a facilitator for students. Students who are active in the game of snakes and ladders can find their own concept of the material being studied. Because the media in the game of snakes and ladders is combined with group discussions.